2021
DOI: 10.3390/ma14092361
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Surface Properties of Poly(Allylamine Hydrochloride)-Based Multilayer Films

Abstract: The layer-by-layer (LbL) method of polyelectrolyte multilayer (PEM) fabrication is extremely versatile. It allows using a pair of any oppositely charged polyelectrolytes. Nevertheless, it may be difficult to ascribe a particular physicochemical property of the resulting PEM to a structural or chemical feature of a single component. A solution to this problem is based on the application of a polycation and a polyanion obtained by proper modification of the same parent polymer. Polyelectrolyte multilayers (PEMs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The aforementioned compounds comprise both ionizable groups, for example, carboxylic acid or styrenesulfonate moieties, and shorter or longer hydrophobic side chains. 38 Charged groups are responsible for stabilization by repulsive electrostatic forces, while hydrophobic side chains can anchor to the surfaces of hydrophobic nanoparticles and provide additional attractive interactions between polyelectrolytes and core-forming materials. Conversely, these side chains can also sterically stabilize the charged particles, further increasing the stability of the particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned compounds comprise both ionizable groups, for example, carboxylic acid or styrenesulfonate moieties, and shorter or longer hydrophobic side chains. 38 Charged groups are responsible for stabilization by repulsive electrostatic forces, while hydrophobic side chains can anchor to the surfaces of hydrophobic nanoparticles and provide additional attractive interactions between polyelectrolytes and core-forming materials. Conversely, these side chains can also sterically stabilize the charged particles, further increasing the stability of the particles.…”
Section: Resultsmentioning
confidence: 99%
“…Considering these drawbacks, a unique class of HF-PEs were carefully studied as stabilizing materials for PLGA nanoparticles as mitomycin carriers. The aforementioned compounds comprise both ionizable groups, for example, carboxylic acid or styrenesulfonate moieties, and shorter or longer hydrophobic side chains . Charged groups are responsible for stabilization by repulsive electrostatic forces, while hydrophobic side chains can anchor to the surfaces of hydrophobic nanoparticles and provide additional attractive interactions between polyelectrolytes and core-forming materials.…”
Section: Resultsmentioning
confidence: 99%
“…The extent of lateral heterogeneity of branched PAMAM films was also quantified with atomic force microscopy at molecule-scale [151]. For films of linear materials, although their statistical features can be obtained via atomic force microscopy, detailed delineation of saturated multilayers of attached linear materials is still lacking [152]. In the meantime, it was acknowledged that PAMAM-PSS films were heterogeneous, examined by direct force measurement [153].…”
Section: Morphology Of Polyelectrolyte Multilayersmentioning
confidence: 99%
“…31,32 The authors of these works evidenced that the swelling ratio of this type of hydrogel is related to the total number of layers and the pH of the assembly solution. 31,33 They also suggested that the swelling behavior of PAH-HA hydrogels can be tuned by controlling the ionic strength, thus allowing interesting applications, especially for the controlled release of active drugs, membrane filtration, and biomaterial coatings. 33−35 Investigating the mechanical properties can provide insight into intermolecular interactions in the materials and is thus of fundamental interest.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As HA and PAH exhibit opposite charge, they can be associated according to the LbL process to produce multilayered hydrogels . Previous works highlighted that these materials, in the absence of any chemical cross-linking, are highly sensitive to pH and ionic strength. , The authors of these works evidenced that the swelling ratio of this type of hydrogel is related to the total number of layers and the pH of the assembly solution. , They also suggested that the swelling behavior of PAH-HA hydrogels can be tuned by controlling the ionic strength, thus allowing interesting applications, especially for the controlled release of active drugs, membrane filtration, and biomaterial coatings. Investigating the mechanical properties can provide insight into intermolecular interactions in the materials and is thus of fundamental interest . However, mechanical measurements on PEMs and hydrogels can be complex and experimentally challenging, especially when the thickness of these materials is of a few micrometers .…”
Section: Introductionmentioning
confidence: 99%